Diversity and inclusion in an emerging market context. (2014) - ,
Abstract : Purpose – The extreme demographic misrepresentation of organisations is a key business and societal issue in South Africa (SA). The purpose of this paper is to provide organisations that are committed to the creation of a diverse and inclusive environment with key considerations that need to be managed in order to create more diverse drive transformation.Design/methodology/approach – This research uses a combination of quantitative and qualitative techniques to gain an understanding of the elements that need to be managed to enhance perception of inclusion in the SA workplace.Findings – The study finds that key inclusion elements that need to be transformed at an organisational level include "senior leadership", "organisation climate", "organisational belonging", "communication" and "transparent recruitment, promotion and development". At an interpersonal level or relational level, inclusion components include respect and acceptance, the "line manager/subordinate relationship" (which includes the subordinates experience of dignity, trust and recognition), "engagement" which includes decision‐making authority and access to information, and finally the "individual's relationship with the organisation's vision and values". Finally, at an individual level, factors which influenced inclusion, and therefore required attention in recruitment or management were "personality", "locus of control", self‐confidence which includes self‐esteem and "power".Research limitations/implications – While this research facilitated "deep" insight into the diversity and inclusion components, this study could have been enriched through exploring diversity and inclusion in other organisational contexts. Second, while the InclusionIndex™ survey provided a useful base measure of inclusion for this research, the use of a survey as the primary research tool might have been leading to the respondents. Third, because the InclusionIndex™ survey was used as the exploratory tool, and was the respondents' first exposure to the diversity and inclusion terminology, the survey became the informal frame of reference for diversity and inclusion, and thus might have influenced the focus group discussion and semi‐structured interview responses.Practical implications – Using these diversity and inclusion considerations, leaders of pluralistic and multicultural organisations can focus their attention on developing inclusion areas that are weak and require more consideration. Second, this research aims to establish that inclusion extends beyond recruitment of diverse individuals to a process driven at organisational, interpersonal and individual levels.Originality/value – These management considerations are important and valuable because they can be used to guide systemic change in organisations, driven at organisational, interpersonal and individual levels. This approach will help organisations to move beyond employment equity compliance, to a commitment to multicultural diverse and inclusive organisations. Acknowledgements : The author would like to thank Tony Burnett and Simon Kettleborough for generously supporting this research through sponsoring the use and administration of the InclusionIndex™ survey.